1994
DOI: 10.1097/00006676-199409000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Stimulatory Effect of Neuromedin C on Pancreatic Exocrine Secretion in Conscious Rats

Abstract: The mechanisms of the stimulatory effect of the bombesin-like peptide neuromedin C on pancreatic exocrine secretion were examined in conscious rats. Rats were prepared with cannulae draining bile and pancreatic juice separately. Intravenous infusion of 0.35 nmoykg/h of neuromedin C significantly increased the secretions of pancreatic bicarbonate and protein, and transiently increased the plasma cholecystokinin (CCK) concentration. The increase in pancreatic secretion persisted for 90 min, whereas the increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
1997
1997

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Infusion (i.v.) of neuromedin C to rats increases plasma cholecystokinin levels within 15-30 min (25). The perfusion of isolated stomach by way of the celiac artery increases somatostatin release with a peak at 4 min from the start of infusion (26).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Infusion (i.v.) of neuromedin C to rats increases plasma cholecystokinin levels within 15-30 min (25). The perfusion of isolated stomach by way of the celiac artery increases somatostatin release with a peak at 4 min from the start of infusion (26).…”
Section: Discussionmentioning
confidence: 98%
“…Numerous complex pharmacological effects of BN͞GRP are due to both direct and indirect mechanisms of action and depend on the species studied and the route of administration (3). Various studies show that the metabolic effects of BN͞ GRP and their antagonists appear very rapidly, but are relatively short lasting (24)(25)(26)(27)(28)(29)). An i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Onthe other hand, the responses of protein secretion to neuromedin C and 2DGwere significantly lower in OLETFthan in LETOrats. There are reports (24)(25)(26) that administration of a memberof the gastrin releasing peptide (GRP) family, including neuromedin C, stimulates pancreatic protein secretion directly and indirectly via CCKrelease. In the present study, we did not measure the plasma CCKlevel after neuromedin C injection, but we found previously (1) that CCK release produced by bile-pancreatic juice diversion is not impaired in OLETFrats.…”
Section: Pancreatic Exocrine Functions In Vivo Effects Of Graded Dosementioning
confidence: 99%